The moon - Rustad, Martha E. H. (Martha Elizabeth Hillman), 1975- (Mankato, Minn. : Capstone Press, 2009)
Photographs and simple text introduce the features of the moon, Earth's only natural satellite.
A shining light -- What is the moon? -- The moon's surface.
Includes bibliographical references (p. 23) and index.
1.6
K-3
Keywords: Moon -- Juvenile literature; Moon; Moon; Readers (Elementary).